B-MYB - p53-related relevant regulator for the progression of clear cell renal cell carcinoma - Nientiedt, Malin; Müller, Katja; Nitschke, Katja; Erben, Philipp; Steidler, Annette; Porubsky, Stefan; Popovic, Zoran V.; Waldbillig, Frank; Mühlbauer, Julia; Kriegmair, Maximilian (Journal of cancer research and clinical oncology, 2021)
To investigate the mRNA expression of B-MYB and MDM2 together with their p53 relatedness in clear cell renal cell carcinoma (ccRCC).
Published online: 19 September 2020
Gesehen am 07.05.2021